2023
DOI: 10.3390/ijms24032859
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Contributing to the Comorbidity of COPD and Lung Cancer

Abstract: Lung cancer and chronic obstructive pulmonary disease (COPD) often co-occur, and individuals with COPD are at a higher risk of developing lung cancer. While the underlying mechanism for this risk is not well understood, its major contributing factors have been proposed to include genomic, immune, and microenvironment dysregulation. Here, we review the evidence and significant studies that explore the mechanisms underlying the heightened lung cancer risk in people with COPD. Genetic and epigenetic changes, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 146 publications
0
9
0
Order By: Relevance
“…Neoantigens were identified in COPD using mass spectrometry supporting the epidemiology data that COPD has been considered as a prestage of lung cancer (7). Non-small cell lung cancer, the most frequent comorbidity, accounts for 40%-70% of COPD patients (8). It was reported that nearly 87% of lung cancerrelated deaths were affected by tobacco smoking in the USA (9).…”
Section: Introductionmentioning
confidence: 62%
“…Neoantigens were identified in COPD using mass spectrometry supporting the epidemiology data that COPD has been considered as a prestage of lung cancer (7). Non-small cell lung cancer, the most frequent comorbidity, accounts for 40%-70% of COPD patients (8). It was reported that nearly 87% of lung cancerrelated deaths were affected by tobacco smoking in the USA (9).…”
Section: Introductionmentioning
confidence: 62%
“…While COPD increase 2 until 7 times fold risk of getting lung cancer. The same mechanism happen both in COPD and lung cancer is oxidative stress [13].…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, the finding from the long‐term follow‐up duration is more likely attributed to the pharmacological mechanisms of SGLT‐2i. Compared to DPP‐4i, the prolonged use of SGLT‐2i leads to weight reduction, which may potentially lower the risk of cancer 4,6,9,52–56 . Due to limitations in the database, the present study cannot examine whether the risk of incident cancer decreases with the duration of SGLT‐2i use.…”
Section: Discussionmentioning
confidence: 94%